(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Let G be a simple graph of order n with vertex set and edge set . A subset of is called an edge dominating set of G if every edge of is adjacent to some edge in . Any edge dominating set with minimum cardinality is called a Minimum Edge Dominating set [1]. Let be a minimum edge dominating set of a graph G. The Minimum Edge Dominating matrix of G is the m x m matrix defined by The characteristic polynomial of is denoted by The Minimum Edge Dominating Eigen values of a graph G are the eigen values of. Minimum Edge Dominating Energy of G [13] is defined as the sum of the absolute values of the Minimum Edge Dominating Eigen values. i.e., In this paper we have computed the Minimum Edge Dominating Energy of a Triangular Book B(3,n) [11] and a Globe graph Gl(n) [12]. In this paper we have considered simple, finite and undirected graphs.